Investigating the causal links between inflammatory cytokines and scoliosis through bidirectional Mendelian randomization analysis - Muradil Mardan; Mardan Mamat; Parhat Yasin; Xiaoyu Cai; Huoliang Zheng; Qingyin Xu; Shaokuan Song; Bo Li; Hao Cai; Pengbo Chen; Zeyu Lu; Shahna Omar; et al. (JOR Spine)
Abstract Background Scoliosis, characterized by a lateral curvature of the spine, affects millions globally. The role of inflammatory cytokines in the pathogenesis of scoliosis is increasingly acknowledged, yet their causal relationships remain poorly defined. Aims This study aims to explore the genetic‐level causal relationships between inflammatory cytokines and scoliosis utilizing bidirectional Mendelian randomization (MR) analysis. Materials and Methods This study leverages genetic data from public Genome‐Wide Association Studies (GWAS). Bidirectional MR was employed to investigate the causal relationships between 44 inflammatory cytokines and scoliosis. The inflammatory cytokine data include 8293 Finnish individuals, while the scoliosis data consist of 165 850 participants of European descent, including 1168 scoliosis cases and 164 682 controls. Causal links were assessed using the inverse variance‐weighted method, supplemented by MR‐Egger, weighted median, and weighted mode analyses. Heterogeneity and pleiotropy were assessed using standard tests, with sensitivity analysis conducted through leave‐one‐out analysis. Results Our analysis demonstrated a significant causal association between the cytokine Resistin (RETN) and the development of scoliosis (p = 0.024, OR 95% CI = 1.344 [1.039–1.739]). No other cytokines among the 44 studied showed significant associations. Discussion The findings highlight the critical role of RETN in scoliosis progression and underscore the complex interplay of genetic and inflammatory pathways. Further research is needed to explore additional biomarkers and their mechanisms in scoliosis. Conclusion This study provides evidence of a significant causal relationship between RETN and scoliosis, emphasizing its potential as a therapeutic target. These findings contribute to understanding scoliosis pathogenesis and pave the way for future research on inflammation‐related pathways and therapies.